Structural characterization of TiO2 thin films on GaAs(100) substrate by MOCVD - Han, YK; Lee, TG; Yom, SS; Sons, MH; Kim, EK; Min, SK; Lee, JY (KOREAN PHYSICAL SOC, 1998)
Titanium dioxide (TiO2) thin films have been grown on GaAs(100) substrate by metal organic chemical vapor deposition (MOCVD). X-ray diffraction patterns showed that the TiO2 thin films for deposition temperature T-s < 400 degrees C had polycrystalline anatase phase dominantly, while the films for T-s > 600 degrees C had mixture of polycrystalline anatase and rutile phases. No interface reaction between the TiO2 film and GaAs substrate for the film deposited at 400 degrees C was observed by scanning electron microscopy and transmission electron microscopy. However, an interdiffusion reaction occurred severely in the TiO2 film gown at T-s = 650 degrees C with a partial crystallization at the interface.